Analysis Student Critical Thinking Skill on Physic Learning with E-Modules type Information Search during The Covid 19 Pandemic - Sukarmin Sukarmin; Dwikie Mahendra Sani (Postgraduate, University of Mataram, 2023)
This research was conducted after the development of e-modules for Newton’s Laws. This was to analyze the students’ critical thinking skills consisting of indicators providing basic alignment, using logic thinking, providing arguments, conducting evaluations, and making decisions. The study was conducted on 62 students at two high schools in Surakarta. The study used descriptive analysis methods using differences in gain values, normality tests, homogeneity, and paired t sample tests and was conducted in 2021. The results showed that students’ critical thinking skills increased after using E-module. The increase was derived from an N-Gain value of 0.60 for overall critical thinking skills and for each aspect of the increase in the moderate category. This research is expected to capture the profile of students’ critical skills and the effectiveness of e-modules in online learning.